Identifying HLA-Associated Polymorphisms in HIV-1 - Brumme, Zabrina L.; Poon, Art F. Y.; Carlson, Jonathan M.; Walker, Bruce D. (HIV Molecular Immunology 2010, 2010)
Cytotoxic T-lymphocytes (CTL) eliminate HIV-1 infected cells through the recognition of antigenic peptides displayed by Human Leukocyte Antigen (HLA) class I molecules on the infected cell surface. HLA-restricted CTL responses drive HIV evolution through selection of viral sequence polymorphisms typically referred to as immune escape mutations. In this short review, we highlight recent methodological advances in our efforts to identify HLA-associated polymorphisms throughout the HIV-1 proteome, and describe how these methods have been used to discover novel epitopes, elucidate complex mutational pathways, and enrich our understanding of HIV-1 as it adapts to HLA-mediated selection pressure at the population level. Achieving a deeper understanding of the sites, pathways and consequences of immune escape is of critical relevance to the continued search for an effective CTL-based AIDS vaccine.